Identité et altčrilč dans le roman québécois - Voldrichová Beránková, Eva (Studia Romanica Posnaniensia, 2017)
As a « relational concept », alterity can only be defined in opposition to what sociologists call a « referential group », an entity which dictates political, religious or cultural norms in a concrete society. Our article will first explain the difference between simple « diversity » and real « alterity », which is perceived as a potential source of threat by the majority society. Using concrete figures from 19th and 20th century Quebec novels, we will illustrate various types of alterity and the general evolution of Canadian mentality in relation to various minorities.